Pengembangan Bahan Ajar Berbasis Problem-Based Learning Untuk Materi Aljabar di SMP - Chandra Sagul Haratua; Riska Chintya Dewi; Ananda De'Visky Hanggara Suci; Sartika Ratnayu (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This study aims to develop Problem-Based Learning (PBL) teaching materials for algebra content in Junior High School (SMP). The research method used is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The results of the study indicate that PBL-based teaching materials can improve students' understanding of algebraic concepts and critical thinking skills. The trial was conducted on eighth-grade students at SMP negeri 3 Depok, with results showing a significant increase in students' final test scores compared to before using the PBL-based teaching materials.